Lumbodorsal flap for repair of meningomyelocele- a procedure matched controlled study - Prasad, Gungi Raghavendra; Sharma, Deepak; Rao, J. V. Subba; Kumar, P. Siva; Aziz, Amtul (International Surgery Journal, 2017)
Background: Open neural tube defects have been approached by innumerable surgical techniques. Hitherto, excision of the exposed neural tube component, water tight closure of dura, approximation of paraspinal soft tissue and skin closure repair was stressed. Support of vertebral defect was not adequately addressed. Objectives were to introduce lumbodorsal/thoraco dorsal fascial flap as an effective answer to the vertebral defect component of MMC. To compare conventional paraspinal soft tissue closure with lumbodorsal/ thoracodorsal fascial flap. Methods: This was a procedure matched controlled study conducted from 1984-2015. A total of 121 procedures were performed by the same team formed the cohort of the study. Conventional muscle mobilization group A (n=50) and lumbodorsal flap group B (n=71) were the two groups. Demographic data, CSF leak, CSF collection, wound dehiscence, duration of drain and duration of surgery were the parameters evaluated with statistically blinded method. Results: The series mostly constituted lumbar (28%) and lumbo-sacral meningomyelocele (56%). Most of the children in both the groups are either at birth or <1 month. Only few patients in group B with lipo-meningocele presented beyond the age of 5 years (7%). 12% in group A had hydrocephalus, whereas 15.4% had in group B. The patients underwent similar technique at all sites of MMC. Grossly it appears that there is less wound dehiscence, less CSF leak, less hygroma formation in group B cases. Duration of surgery is similar in both the groups, most of them requiring 60 to 120 minutes. The duration of drainage was more than 7 days in group A (34%) as compared to group B (20%). Conclusions: Lumbodorsal/thoraco dorsal fascial flap adequately supports the vertebral defect and skin flaps. They seem to be superior in addressing the vertebral defect component.